2018
DOI: 10.15331/jdsm.7020
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Status of Children With High Risk of Sleep-Disordered Breathing

Abstract: JDSMStudy Objectives: To evaluate caries, gingival and periodontal status, and oral health-related quality of life (OHRQoL) in children with high risk of sleep-disordered breathing (SDB) in comparison to those with low risk of SDB. Methods:This cross-sectional study recruited consecutive children between the ages of 8 to 17 years from a university-based pediatric dental clinic. Caregivers completed the Pediatric Sleep Questionnaire (PSQ) to stratify risk of SDB. Children and their caregivers completed the Chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Children at risk for OSA had more dental caries, periodontal disease, and poorer OHRQoL than unaffected peers. 26 Interestingly, the oral health parameters of children with PSG-proven OSA were very similar to what we reported in children at high risk of OSA (based on PSQ). This highlights the benefit of using the PSQ as a noninvasive and practical tool for early detection of OSA.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Children at risk for OSA had more dental caries, periodontal disease, and poorer OHRQoL than unaffected peers. 26 Interestingly, the oral health parameters of children with PSG-proven OSA were very similar to what we reported in children at high risk of OSA (based on PSQ). This highlights the benefit of using the PSQ as a noninvasive and practical tool for early detection of OSA.…”
Section: Discussionsupporting
confidence: 83%
“…34 Recently, our group reported that children at high risk of SDB have significantly poorer OHRQoL than children at lower risk of SDB. 26 As far as we are aware, no studies have been conducted to evaluate OHRQoL in pediatric patients with OSA. We believe the current study is the first to report the association between OSA and poor child-and caregiver-rated OHRQoL.…”
Section: Discussionmentioning
confidence: 99%